The transformation of American politics : activist government and the rise of conservatism - Pierson, Paul; Skocpol, Theda (Princeton studies in American politics., 2007)
The contemporary American political landscape has been marked by two paradoxical transformations: the emergence after 1960 of an increasingly activist state, and the rise of an assertive and politically powerful conservatism that strongly opposes activist government. Leading young scholars take up these issues in The Transformation of American Politics. Arguing that even conservative administrations have become more deeply involved in managing our economy and social choices, they examine why our political system nevertheless has grown divided as never before over the extent to which government should involved itself in our lives.